(untitled) (Journal of the Bangladesh Agricultural University, 2024)
In agriculture, a wide range of pesticides have been used to improve crop quality and productivity. Farmers in Bangladesh are using pesticides in vegetables following no rules and regulations as a result it has been a potential risk to the environment and human health. For this reason, an experiment was conducted to determine the pre-harvest interval of cypermethrin and chlorpyrifos in tomatoes (Solanum lycopersicum) and yard-long beans (Vigna unguiculata) considering the maximum residue limit (MRL) set by the European Union. The crops were sprayed with the recommended dose of chlorpyrifos (2 ml/L) and cypermethrin (1 ml/L) in four supervised field trials. Samples were collected at 0, 1, 2, 3, 4, 5, 6, 7, 8, 9, and 10 days after spray (DAS). Gas chromatography was used for a simple and effective multiple pesticide residue analysis where Flame Thermo ionized Detector for chlorpyrifos, and Electron Capture Detector for cypermethrin were used for the determination of the pesticide residues. The quantities were above MRL up to 3 DAS for cypermethrin and 7 DAS for chlorpyrifos in tomatoes. The detected residues were above MRL in yard-long beans up to 4 DAS for cypermethrin and 9 DAS for chlorpyrifos. The pre-harvest interval was determined in tomatoes at 4 DAS for cypermethrin, 8 DAS for chlorpyrifos, and in the case of yard-long beans, it was 5 DAS for cypermethrin and 10 DAS for chlorpyrifos. J Bangladesh Agril Univ 22(4): 460–467, 2024